The Role of the Technical and Vocational Education and Training (TVET) Curriculum in Enhancing Workforce Readiness - Geleta Buraka Teferi; Qiaolun Gu; Zhen Wu (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2026)
The Technical and Vocational Education and Training (TVET) curriculum is essential for producing a skilled labor force, many graduates continue to experience disconnect between their learned skills and the demands of the job market. This discrepancy restricts economic productivity and damages employability. This study looks at how integrating theoretical and practical instruction, fostering both technical and soft skills, and matching learning outcomes with industry requirements can all help a well-structured TVET curriculum overcome these obstacles. The study emphasizes how important curriculum design is in improving graduates' flexibility, problem-solving skills, and capacity for lifelong learning qualities necessary for navigating quickly changing technological and economic landscapes. A strong TVET program enhances organizational performance, boosts individual career prospects, and advances socioeconomic development by giving students industry-relevant competencies. The report promotes ongoing cooperation between academic institutions, decision-makers, and industry stakeholders and emphasizes the significance of strategic curriculum planning as a remedy for workforce under preparedness. The results ultimately show that a strong TVET program not only lays the groundwork for employability but also serves as a stimulant for long-term economic expansion and national competitiveness.